Description of the male of Megalava truncata Perrichot (Hymenoptera: Megalyridae) in Early Cretaceous amber from El Soplao (Spain) - la Fuente, Ricardo Pérez-De; Perrichot, Vincent; Ortega-Blanco, Jaime; Delclòs, Xavier; Engel, Michael S. (Zootaxa, 2012)
A new fossil of megalyrid wasp recently discovered in Early Cretaceous (Albian) amber from El Soplao (Cantabria, Spain) isdescribed as the male of Megalava truncata Perrichot, 2009, originally described from Peñacerrada I (= Moraza) amber (Bur-gos, Spain). The new specimen permits a more thorough description of the genus Megalava, which was established originallyfrom a single, fragmentary specimen lacking the metasoma, and also permits a discussion on the characters of phylogenetic value for the clade [Megazar + Megalava].